Aesthetic Theory - Adorno, Theodor W. 1903-1969; Hullot-Kentor, Robert; Adorno, Gretel; Tiedemann, Rolf (London Athlone, 1997)
Perhaps the most important aesthetics of the twentieth century appears here newly translated, in English that is for the first time faithful to the intricately demanding language of the original German. The culmination of a lifetime of aesthetic investigation, Aesthetic Theory is Adornos major work, providing a clarifying lens through which the whole of Adornos corpus is best viewed.Inserting the silver rib of a foreign word into an idea, Walter Benjamin argued in a passage Adorno was fond of quoting, helps the idea to survive. Meant to undermine the ideology of an entirely organic language, free of all alien intrusions, this insight can be fruitfully extended to distinguished translations of entire texts. In the case of Adornos posthumous magnum opus, Aesthetic Theory, Robert Hullot-Kentors long-awaited new translation is pure sterling. Rarely has so much thoughtfulness and sensitivity been marshaled to retranslate a work that fully deserves a second chance.
Originally published in 1970
Keywords: 20th Century (1901-2000); Esthetics; Germany